Tissue Expression and Actin Binding of a Novel N-Terminal Utrophin Isoform. (14th November 2011) - Zuellig, Richard A.; Bornhauser, Beat C.; Amstutz, Ralf; Constantin, Bruno; Schaub, Marcus C.
Abstract : Utrophin and dystrophin present two large proteins that link the intracellular actin cytoskeleton to the extracellular matrix via the C-terminal-associated protein complex. Here we describe a novel short N-terminal isoform of utrophin and its protein product in various rat tissues (N-utro, 62 kDa, amino acids 1–539, comprising the actin-binding domain plus the first two spectrin repeats). Using different N-terminal recombinant utrophin fragments, we show that actin binding exhibits pronounced negative cooperativity (affinity constants K 1 = ∼ 5 × 10 6 and K 2 = ∼ 1 × 10 5 M - 1 ) and is Ca 2+ -insensitive. Expression of the different fragments in COS7 cells and in myotubes indicates that the actin-binding domain alone binds exlusively to actin filaments. The recombinant N-utro analogue binds in vitro to actin and in the cells associates to the membranes. The results indicate that N-utro may be responsible for the anchoring of the cortical actin cytoskeleton to the membranes in muscle and other tissues.